Neurobehavioural Changes in a Patient with Bilateral Lesions of the Globus Pallidus - R. Haaxma; T. W. Robbins; M. James; W. H. Brouwer; J. G. Colebatch; C. D. Marsden (Behavioural Neurology)
This study has characterized the long-term neurobehavioural changes in a woman who, following the intake of an unidentified substance, sustained subtotal bilateral lesions of the globus pallidus and small lesions at selective sites adjacent to it. Associated with these lesions was a significantly reduced blood flow in multiple frontal cortical regions, most prominently in area 10, the anterior cingulate and the supplementary motor cortex. Her cognitive deficits were generally consistent with those found in patients with frontal lobe dysfunction but some deficits, i.e. in visual memory and learning, were more compatible with temporal lobe dysfunction. Incapacitating personality or obsessive compulsive changes as reported by others with similar lesions were absent and she could live independently. The cognitive changes are consistent with the view that the globus pallidus has important functions in mediating how internal representations of stimulus input are converted into various forms of action, for example, in planning solutions to problems and in working memory.